Augmented reality-based radial and lateral motion stimuli alter aiming performance in dart throwing - Yuki Ueyama; Masanori Harada (Scientific Reports)
Abstract This study used an augmented reality (AR) head-mounted display to generate three-dimensional (3D) perceived motions involving optic flow and evaluated their effects on aiming motor skill in dart throwing. The motions were generated by random white spheres moving in 3D space. Six motion patterns were assessed: random, lateral, radial expansion, radial contraction, combined random and radial expansion, and diagonal radial expansion. The effects of these motion patterns on aiming accuracy were compared to a control condition lacking sphere motions. We observed significant effects of radial expansion and contraction motions, as well as lateral motion, but not of the other motions. The radial expansion and lateral motions biased the dart positions, whereas the radial contraction motion reduced lateral variance. These findings imply that AR-based perceived motion has the potential to enhance motor skills by reducing error and variance. Therefore, although other types of motion may also exert effects, this study provides a basis for further research on AR-based illusions of motion perception.